Fallout melt debris and aerodynamically-shaped glasses in beach sands of Hiroshima Bay, Japan. (March 2019) - Wannier, Mario M.A.; de Urreiztieta, Marc; Wenk, Hans-Rudolf; Stan, Camelia V.; Tamura, Nobumichi; Yue, Binbin
Highlights: First description of fallout debris from a nuclear explosion in an urban environment ("Hiroshimaites"). Identification of different classes of melt debris (e.g. vesicular filament glasses). Mass estimate of melt fallouts and correlation with the mass of the atomic cloud. Description of a unique mullite-anorthite microcrystals assemblage, pointing to a high-temperature origin (>1800 °C). New avenue for research linking the chemical composition of melt fallouts to constituents of the urban landscape. Abstract: A complex association of millimeter-sized, aerodynamically-shaped debris, including glass spherules, glass filaments, and composite-fused melt particles was recovered from beach sands on the shores of the Motoujina Peninsula in Hiroshima Bay, Japan. Based on optical microscopy, this debris comprises six morphological groups ranging from clear glasses to rubber-like constituents. Scanning electron microscopy and synchrotron X-ray microdiffraction revealed dominant aluminum, silicon and calcium (Al-Si-Ca) elemental composition with some iron, mainly in glass, associated with precipitates of mullite and anorthite microcrystals, hematite dendrites and iron-chromium globules, indicative of original temperature conditions >1800 °C. Aerodynamically-shaped fallout debris, including glass spherules described in this study, are generally produced by single high-energy catastrophic events, such as an extraterrestrial body impacting Earth or a nuclear explosion. This study interprets the large volumes of fallout debris generated under extreme temperature conditions as products of the Hiroshima August 6th, 1945 atomic bomb aerial detonation. The chemical composition of the melt debris provides clues to their origin, particularly with regard to city building materials. This study is the first published record and description of fallout resulting from the destruction of an urban environment by atomic bombing.